A Young Man with High-grade Fever and HIV infection - Leelasiri, Apichai; Pongpruttipan, Tawatchai (Greater Mekong Subregion Medical Journal, 2021)
A 23-year-old man, a hilltribe in northern Thailand with HIV infection but poor compliance to antiviral treatment presented with acute onset of fever, fatigue with palpitation. He also experienced easily fatigue and tiredness for 1 month. He went to local hospital and was treated symptomatically without any improvement. Then he went to another hospital for management. Initial investigation showed anemia and thrombocytopenia. The bone marrow examination revealed yeast-like microorganism with binary fission. Final diagnosis of disseminated talaromycosis (penicillosis) was made. So, in case of fever of unknown origin in HIV-infected patients, bone marrow examination should be performed which can be helpful for definite diagnosis.